Practical Approach to Mammalian Cell and Organ Culture - Mukherjee, Tapan Kumar; Malik, Parth; Mukherjee, Srirupa (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This Major Reference Work offers a detailed overview of culturing primary, secondary cell lines, tissues, and organs. It first introduces various types of mammalian cell cultures, infrastructure requirements for a mammalian cell-culture laboratory. The subsequent chapters present the detailed protocols for the isolation of mammalian hematologic organs and cells. It also discusses various cell-based assays for monitoring cell viability, cell proliferation, cytotoxicity, cell senescence, and cell death assays. In addition, the book addresses the various problems encountered while culturing animal cells, their possible causes, and suggested solutions, presenting detailed protocols for isolation and primary culturing of various mammalian cells and hematoimmunologic organs in two dimensions. Lastly, it reviews the various applications of animal-cell culture, stem-cell culture, and tissue and organ culture. As such, this reference book is highly relevant for students and professionals new to cell-culture work as well as to those wishing to expand their skills from cell-line cultures to primary cultures and from conventional 2D cultures to 3D cultures.
Mammalian Cell Culture: An Overview -- Establishment of a Cell Culture Laboratory -- Mammalian Cell Culture Laboratory: Equipment and Other Materials -- Common Reagents and Medium for Mammalian Cell Culture -- Microbial Contamination of Mammalian Cell Culture -- Mammalian Cell Culture Types and Guidelines for Their Maintenance -- Isolation and Purification of Various Mammalian Cells: Single Cell Isolation -- Isolation and Primary Culture of Various Mammalian Cells -- Primary Culture of Immunological Cells -- Culture of Neuron and Glia Cells -- Culture of Continuous Cell Lines -- Stem Cell Culture and Its Applications -- Mammalian Cell Culture in Three Dimensions: Basic Guidelines -- Organ, Histotypic and Organotypic Culture, and Tissue Engineering -- Large-Scale Culture of Mammalian Cells for Various Industrial Purposes -- Experimental Mammalian Cell Culture-Based Assays -- Mammalian Cells, Tissues and Organ Culture: Applications -- Biosensors' Utility in Mammalian Cell Culturing -- Nanomaterials:Compatibility Towards Biological Interactions -- Review on IPR and Technological Advancements in Nanotechnology for Nanomedicine -- Emerging Drug Delivery Potential of Gold and Silver Nanoparticles to Lung and Breast Cancers -- Mammalian Cells: Reliability as Model System in the Ecotoxicological Evaluation of Environmental Stressors -- Bioimaging: Usefulness in Modern Day Research -- Troubleshooting of Mammalian Cell Culture.
Keywords: Immunology; Cytology; Stem cells; Biology; Immunology; Cell Biology; Stem Cell Biology; Biological Sciences